Tomonaga–Luttinger liquid behavior and spinon confinement in YbAlO3 - L. S. Wu (Nature Portfolio, 2019)
Low dimensional quantum magnetic excitations are intriguing but the experimental realizations are challenging. Here, the authors demonstrate Tomonaga–Luttinger behavior and spinon confinement in rare-earth perovskite YbAlO3 by inelastic neutron scattering measurements.